HINDUTVA: THE SPIRIT OF HINDUISM - G. C. Nayak (Journal of Dharma, 2004)
By Hindutva, I mean that which constitutes the very sprit, the essence of Hinduism. The fundamental question, however, that we have to address is: “What exactly would constitute this spirit?” For me, it is a million-dollar question that has flabbergasted many, including laymen as intellectuals, and even the leaders themselves. However, there should be nothing mysterious about it, unless one refuses to accept that Hinduism is as vast as the ocean and as limitless as the sky. The paradox seems to stare us in our face in the fact that the essence of Hinduism lies not only in the Hindu religious beliefs and practices but also beyond the narrow framework in which the Hindu religion is manifested in its popular form. It is paradoxical; as yet it is true of Hindutva, the spirit of Hinduism. It points to a typical form of transcendence intrinsic to Hinduism itself which I would designate as transcendental secularism. Secularism of this typical variety, it needs to be noted, is not an accidental feature of Hinduism, but is unavoidably associated with its intrinsic nature. Here lies the perennial attraction of Hindutva as well as its apparent mystery when it comforts us in our face along with its religious dogmas and practices. It needs to be discussed in some detail, which I propose to do in the sequel.